Forsøgs- og udviklingsprogrammer i dansk idrætspolitik - Ibsen, Bjarne (Forum for Idræt, 2012)
Danish sports policy is primarily aimed to support sports clubs and organizations economically and making sports facilities available to associations. Over the past three decades, however, this policy has been supplemented by state experimental and development programs. In the first wave of experimental programs in the 1980s the purpose of the programs was to stimulate experimental and innovative thinking, and the long term goal of a program was to change legislation and administration in accordance with experience of the program. Therefore, the programs were also thoroughly evaluated. Experimental and development programs were part of a decentralization ideal that can be described as communitarian. This first wave of experimental programs in the 1990s was gradually replaced by more targeted and government-controlled programs, which are more aimed at improving performance in specific areas and providing political posturing. This new type of development program is better characterized by liberal and economically oriented management ideals (New Public Management). A number of evaluations of these programs and projects show that they rarely live up to their own goals and expectations. At the same time, the evaluations are often insufficient to become wiser on the projects positive and negative experiences. At the end of the article the author suggests, that experimental and development programs to a greater extent are aimed to test – and investigate – alternative solutions to society’s diverse problems.